Draft Annual Plan 2008-2009 Himachal Pradesh - Planning Commission (Planning Commission, 2008)
After India became free in 1947, there was a demand in some quarters for the merger of Hill States with the east Punjab but it met with vehement opposition from the rulers and people. In what is Himachal Pradesh today, the Praja Mandal workers and the rulers had different opinions about the future of these hilly States. After a brief spell of hectic negotiation, the rulers and the Praja Mandal workers decided to inform Government of India to form a union of these small hill States with the name of Himachal Pradesh.
Planning Department, Government of Himachal Pradesh